'Satan's bludy clawses': how religious persecution, exile and radicalisation moulded British Protestant identities. Issue 3 (14th September 2018) - Dawson, Jane E. A.
Abstract: The study examines the radicalisation experienced by one group of religious exiles in the middle of the sixteenth century. The English-speaking congregation in Geneva formed in 1555 produced a Bible, metrical psalter and order of worship that shaped the Anglophone Reformed tradition. Study of the congregation's output shows how watching the martyrdoms in England generated a dynamic anger and fresh interpretations of persecution, tyranny and resistance. Conveyed by the worship texts, this radical legacy passed into the identities of Reformed Protestants in the British Isles, the Atlantic world and subsequently across the globe.